BLAT-Based Comparative Analysis for Transposable Elements: BLATCAT - Lee, Sangbum (Hindawi Publishing Corporation, 2014)
The availability of several whole genome sequences makes comparative analyses possible. In primate genomes, the priority of transposable elements (TEs) is significantly increased because they account for ~45% of the primate genomes, they can regulate the gene expression level, and they are associated with genomic fluidity in their host genomes. Here, we developed the BLAST-like alignment tool (BLAT) based comparative analysis for transposable elements (BLATCAT) program. The BLATCAT program can compare specific regions of six representative primate genome sequences (human, chimpanzee, gorilla, orangutan, gibbon, and rhesus macaque) on the basis of BLAT and simultaneously carry out RepeatMasker and/or Censor functions, which are widely used Windows-based web-server functions to detect TEs. All results can be stored as a HTML file for manual inspection of a specific locus. BLATCAT will be very convenient and efficient for comparative analyses of TEs in various primate genomes.